Ectopic parathyroid gland within carotid sheath. Issue 1 (22nd November 2020) - Poh, Benjamin Ruimin; Nagadia, Rahul Harshad; Tay, Gerald Ci‐An
Abstract: During operative exploration of the neck for parathyroid surgery, the surgeon should always consider possible ectopic locations of the glands and have a reasonable surgical strategy for locating these ectopic glands. Abstract : During operative exploration of the neck for parathyroid surgery, the surgeon should always consider possible ectopic locations of the glands and have a reasonable surgical strategy for locating these ectopic glands.